2000
DOI: 10.2307/3454439
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Livestock Operations, Health, and Quality of Life among Eastern North Carolina Residents

Abstract: People who live near industrial swine operations have reported decreased health and quality of life. To investigate these issues, we survreyed residents of three rral communities, one in the vicinity of an approximately 6,000-head hog operation, one in the vicinity of two intensive cattle operations, and a third rural agricultural area without livestock operations that use liquid waste management systems. Trained interviewers obtained information about health symptoms and reduced quality oflife during the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 18 publications
(22 reference statements)
3
124
0
Order By: Relevance
“…Quality of life, as indicated by the number of times residents could not open their windows or go outside even in nice weather, was found to be similar for residents in the vicinity of a cattle operation or far away from a livestock unit but greatly reduced among residents near a hog operation (Wing and Wolf, 2000). More wheezing has been observed among pupils at schools in the vicinity of confined swine feeding operations (Mirabelli et al, 2006).…”
Section: Health Effect In the Surrounding Residential Areamentioning
confidence: 80%
See 1 more Smart Citation
“…Quality of life, as indicated by the number of times residents could not open their windows or go outside even in nice weather, was found to be similar for residents in the vicinity of a cattle operation or far away from a livestock unit but greatly reduced among residents near a hog operation (Wing and Wolf, 2000). More wheezing has been observed among pupils at schools in the vicinity of confined swine feeding operations (Mirabelli et al, 2006).…”
Section: Health Effect In the Surrounding Residential Areamentioning
confidence: 80%
“…Airborne particles usually act as a vector for pathogenic bacteria, viruses, endotoxins, odours material, gases and liquid substances (Verein Deutscher Ingenieure, 1997). Viable bacteria and vira carried by the dust particles may have greater ability to survive and thereby constitute a local health risk (Wang, Z. et al 1997;Wing, S. and S. Wolf, 2000).…”
Section: Bioaerosols and Livestock Productionmentioning
confidence: 99%
“…12 The potential contamination of groundwater sources by fecal waste pathogens is of great concern in eastern North Carolina because this area has a high dependence on well water for drinking. 13 In addition, "groundwater contamination is a particular problem in eastern North Carolina because the water tables are high and many wells are shallow or unlined." 13 Two days after Hurricane Floyd struck the North Carolina coast, hog waste lagoons ruptured, which led to the dispersal of animal waste to the groundwater, surface water, and residential well water supplies.…”
Section: Hog Farms and Floodingmentioning
confidence: 99%
“…13 In addition, "groundwater contamination is a particular problem in eastern North Carolina because the water tables are high and many wells are shallow or unlined." 13 Two days after Hurricane Floyd struck the North Carolina coast, hog waste lagoons ruptured, which led to the dispersal of animal waste to the groundwater, surface water, and residential well water supplies. 11,14,15 The extensive flooding also led to the drowning of thousands of hogs and poultry.…”
Section: Hog Farms and Floodingmentioning
confidence: 99%
“…A study in North Carolina compared reported physical symptoms and quality-oflife perceptions among 155 individuals from three rural communities: a rural community with no livestock facilities within 2 miles; a similar group of households within 2 miles of a dairy facility; and another group within 2 miles of a swine CAFO (213). The frequencies of reported symptoms in the three groups were compared with adjustment for sex, age, smoking status, and employment.…”
Section: Community Health Effectsmentioning
confidence: 99%